2002
DOI: 10.1002/cne.10164
|View full text |Cite
|
Sign up to set email alerts
|

Cell types and response properties of neurons in the ventral division of the medial geniculate body of the rabbit

Abstract: Although there is evidence for multiple classes of thalamic relay neurons in the auditory thalamus, correlative anatomical and physiological studies are lacking. We have used the juxtacellular labeling technique, in conjunction with Nissl, Golgi, and immunocytochemical methods, to study the morphology and response properties of cells in the ventral division of the medial geniculate body of the rabbit. Single units in the ventral division of the medial geniculate body (MGV) were characterized extracellularly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…No preference for contralateral or binaural stimulation was classified as excitatory/occlusion (EO) (Imig and Adrian, 1977;Middlebrooks and Zook, 1983). Afterward, spike rasters, poststimulus time histograms (PSTHs) and tuning curves were obtained (Cetas et al, 2002a). The binaurality determined for noise bursts was used to set the mode of stimulus presentation (contra or binaural) when the automated tuning curve program was run.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No preference for contralateral or binaural stimulation was classified as excitatory/occlusion (EO) (Imig and Adrian, 1977;Middlebrooks and Zook, 1983). Afterward, spike rasters, poststimulus time histograms (PSTHs) and tuning curves were obtained (Cetas et al, 2002a). The binaurality determined for noise bursts was used to set the mode of stimulus presentation (contra or binaural) when the automated tuning curve program was run.…”
Section: Methodsmentioning
confidence: 99%
“…(2) More importantly, experimental animals served as their own controls; adjacent cortical penetrations in which one electrode passed through a TC patch while the other did not were comparable in frequency progression, latency, sharpness of tuning, and response strength. (3) In some cases, the multi-unit responses within a TC patch (Cetas et al, , 2002a(Cetas et al, , 2002b. TC axons originating from binaural-specific relay neurons (red, blue) located in frequency slabs terminate in patches along a frequency strip in AI.…”
Section: Integrity Of Tracer-injected Mgvmentioning
confidence: 99%
See 1 more Smart Citation
“…MGBv neurons in turn project to AI, where these features are represented in layer III and layer IV (Read et al, 2002), forming a two dimensional projection plane (Huang and Winer, 2000;Smith and Populin, 2001). Previous studies in cat and rabbit found a single low-to-high BF organization or tonotopy in MGBv (Aitkin and Webster, 1972;Imig and Morel, 1985;Brandner and Redies, 1990;Cetas et al, 2002;Cetas et al, 2003). Neurons with similar BFs form isofrequency laminae which extend ~3 mm in the dorsal-ventral dimension of MGBv in both species and which correspond anatomically to fibrodendritic laminae (Morest, 1965).…”
mentioning
confidence: 92%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (Imig and Morel, 1985) or up to 1 octave in rabbit (Cetas et al, 2001;Cetas et al, 2002) MGBv. Reconstruction of physiological recording tracks in cat MGBv (Imig and Morel, 1985) suggests two distinct regions within the laminar subdivision, one with a fine and the other with a coarser tonotopic frequency resolution (Escabí and Read, 2005).…”
mentioning
confidence: 99%